Lumacaftor/ivacaftor initiation in two liver transplantation patients under tacrolimus and antifungal azoles - Ikrame Chouchane; Nathalie Stremler‐Lebel; Philippe Reix (Clinical Case Reports, 2019)
Key Clinical Message We report the initiation of CFTR modulator lumacaftor/ivacaftor combination (LUM/IVA) in two adolescents with cystic fibrosis who were treated with antifungal azoles (AZO) and tacrolimus (TCS) for liver transplantation. Despite multiple drug‐drug interactions, maintaining therapeutic TCS levels was achievable. During the following year, LUM/IVA was well tolerated, providing clinical benefits.